1995
DOI: 10.1021/jm00026a012
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Antimalarial Activities of N-Substituted 11-Azaartemisinins

Abstract: A two-step reaction sequence between artemisinin and methanolic ammonia followed by treatment with Amberlyst 15 yielded 11-azaartemisinin in 65% yield. Substituting a variety of primary alkyl- and heteroaromatic amines for ammonia in the reaction sequence yields N-substituted 11-azaartemisinins in similar or greater yield. When Amberlyst 15 is replaced by a mixture of sulfuric acid/silica gel, both 11-azaartemisinin and the expected metabolite, 10-azadesoxyartemisinin, are formed in 45% and 15% yields, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 2 publications
0
54
0
Order By: Relevance
“…Surprisingly, attempted removal of the carbonyl group in the methanesulfonyl derivative 7 using these same reagents also failed; the attachment of an electron-withdrawing group to the nitrogen atom was expected to attenuate the deactivating effect of the nitrogen atom on carbonyl reactivity characteristic of amides. Attempted reduction of imidate esters [10] derived from 5 with hydride donors also failed. Treatment of 7 in dichloromethane containing an excess of trimethylsilyl chloride with lithium borohydride in THF [18] resulted in isomerization to the products 8 (24 %) and 9 (22 %).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, attempted removal of the carbonyl group in the methanesulfonyl derivative 7 using these same reagents also failed; the attachment of an electron-withdrawing group to the nitrogen atom was expected to attenuate the deactivating effect of the nitrogen atom on carbonyl reactivity characteristic of amides. Attempted reduction of imidate esters [10] derived from 5 with hydride donors also failed. Treatment of 7 in dichloromethane containing an excess of trimethylsilyl chloride with lithium borohydride in THF [18] resulted in isomerization to the products 8 (24 %) and 9 (22 %).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst an increase in lipophilicity generally enhances antimalarial activity, it also enhances toxicity. [6,7] It has been shown that the attachment of alkyl chains (C [10][11][12][13][14][15][16] ) to artemisinins at C10 by an amide linker results in drastic enhancement in cytotoxicity, as gauged by effects in vitro on Hep G2 cancer cell lines. [28] However, such compounds are so toxic they cannot be screened in vivo.…”
Section: Antimalarial Activity and Relative Cytotoxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound 6i was obtained by reductive ozonolysis of the N-allyl analog 6b (Scheme 2). An attempt of the McPhail group to reproduce the results of Ziffer et al, 5 surprisingly led to the formation of some by-products (Scheme 3). 6 Reaction of artemisinin with anhydrous ammonia, yielded the expected products 6a and 7, along with the isolation of 25% of 9.…”
Section: Methodsmentioning
confidence: 98%
“…When Amberlyst was used instead of H 2 SO 4 /SiO 2 , the yield of the desired compound increased to 65% and formation of the deoxy analogue was not observed. 5 An attempt to allylate the N-atom of 6a with allyl bromide in the presence of silver oxide exclusively led to the undesired O-allyl derivative 8 (Scheme 2). Fortunately, the former approach is easily extended to prepare N-substituted 11-azaartemisinins using alkyl-, aromatic, or heteroaromatic amines instead of ammonia.…”
Section: Methodsmentioning
confidence: 99%